The Teacher Professional Certification Policy - Rahmawati, Rahmawati; Saidina, Saidina; Yuniar, Yuniar; Junaida, Junaida (The Future of Education Journal, 2025)
This article explores the policy of professional certification for teachers in Indonesia as a strategic effort to improve the quality of education. The certification program serves as formal recognition of professional competence, including pedagogical, personal, social, and professional domains. Since the enactment of Law No. 14 of 2005 on Teachers and Lecturers, the government has implemented various certification schemes, such as the Teacher Professional Education (PPG) and PLPG programs, to ensure that educators meet national standards. The findings of this study, based on a descriptive-analytical literature review, indicate that certification has contributed to improvements in teacher competence, motivation, and professional development. However, several challenges remain in its implementation, including bureaucratic inefficiencies, uneven access across regions, lack of continuous evaluation, and the limited impact on actual teaching quality. Therefore, while professional certification is essential for elevating the status and performance of educators, it must be supported by effective governance, equitable access, and sustainable follow-up mechanisms. Enhancing these aspects will ensure that certification policies truly contribute to the advancement of education in Indonesia.